Hand-crafted candy bars : from-scratch, all-natural, gloriously grown-up confections - Norris, Susie (Chronicle Books, 2013)
"The beloved candy bars of your childhood have finally grown up. Using high-quality chocolate, creamy homemade caramel and nougat, crunchy nuts, and lots and lots of sugar, these recipes raise the (candy) bar to new levels of sweet sophistication."--p.[4] of cover.